INTEGRAL RIEMANN-LEBESGUE - Ikram Hamid (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2012)
In this paper, we discuss a Riemann-type integrals, we called RL-integral. Then, we will construct the RL-integral on [a,b] by studying some basic properties of RL-integrable functions, the characteristics of RL-primitive, the relation between the RL-integral and the Henstock Integral, and some convergence theorems for RL-Integral.